Diagnosis dan Penatalaksanaan Benda Asing Baterai Kancing pada Kavum Nasi - Yolazenia Yolazenia; Elfahmi Elfahmi (Fakultas Kedokteran Universitas Riau, 2017)
Nasal foreign body is common case that often seen in children. Button battery is one of nasal foreign body that rarelyseen and most commonly occur in children 2-5 year-old. A nasal button battery is one of otorhinolaryngologicalemergency because it can lead to severe damage, necrosis, and perforation of nasal septum. Therefore, early diagnosisand prompttreatment was needed. A case of button battery in nasal cavity in a 3 year-old boy was reported, which hadbeen performed an extraction of foreign body and irrigation under general anesthesia.